Empowerment of Women-Led MSMEs in Mojokerto through Artificial Intelligence Training to Improve Product Marketing Communication Skills - Dewi, Ratnainingrum Zusyana; Ningsih, Masnia; Utama, Jenny Yudha (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service initiative aims to empower women-managed Micro, Small, and Medium Enterprises (MSMEs) in Mojokerto, Indonesia, by improving their digital marketing communication skills through the practical application of Artificial Intelligence (AI) tools. Despite their crucial contribution to the economy, many women entrepreneurs face barriers in adopting digital technologies, which limits their market reach and business growth. Through a collaboration with the Mojokerto Cooperative Office and the Gerakan Majapahit Muda, supported by Microsoft and the Ministry of Digital Communications, the program trained 45 women entrepreneurs using a community-based participatory approach. A tailored three-day AI training module introduced tools such as ChatGPT, Canva, and WhatsApp Bots, followed by a two-month online mentorship. Results showed significant improvements in AI literacy, marketing content quality, customer engagement, and business performance. Notably, social media interactions and online product orders increased, with several entrepreneurs reporting up to 30% sales growth. The program also fostered peer learning and collective support among participants. While challenges such as limited internet access and resistance to technology were encountered, they were mitigated through inclusive teaching strategies. The project demonstrates the transformative potential of AI training in enabling inclusive, sustainable development for women entrepreneurs in semi-urban areas.